Factors Associated with Variability in Rifampin Plasma Pharmacokinetics and the Relationship between Rifampin Concentrations and Induction of Efavirenz Clearance. Issue 3 (13th January 2014) - Kwara, Awewura; Cao, Lei; Yang, Hongmei; Poethke, Pamela; Kurpewski, Jaclynn; Tashima, Karen T.; Mahjoub, Behrang D.; Court, Michael H.; Peloquin, Charles A.
<x xml:space="preserve">Abstract</x> Study Objectives To identify factors associated with variability in rifampin plasma pharmacokinetics and explore the relationship between rifampin pharmacokinetics and change in efavirenz plasma pharmacokinetics with rifampin coadministration. Methods In this randomized, cross‐over study, 12 healthy volunteers received either efavirenz 600 mg/day or efavirenz 600 mg with rifampin 600 mg/day for 8 days. After a washout period of at least 2 weeks, subjects crossed over to the alternate 8‐day regimen. Samples were obtained for pharmacokinetic assessment on day 8 of each study cycle. Drugs concentrations were determined by a validated high‐performance liquid chromatography. Pharmacokinetic parameters were calculated using noncompartmental analysis. Multivariate analysis was used to examine factors associated with rifampin pharmacokinetics. Spearman correlation analysis was used to investigate relationship between rifampin pharmacokinetics and change in efavirenz plasma pharmacokinetics with rifampin coadministration. Measurements and Main Results Of 11 evaluable subjects, the median interquartile range, rifampin peak concentration (Cmax), area under the concentration‐time curve (AUC0–24 hour), and weight‐normalized clearance were 8.9 (7.3–13.8) μg/ml, 48.8 (29.6–67.4) μg·h/ml, and 0.19 (0.11–0.29) L/h/kg, respectively. Solute carrier organic anion transporter family member 1B1 (SLCO1B1) c.388A→G and SLCO1B1 c.463C→A polymorphisms jointly had significant effect on rifampin Cmax (R2 = 0.75). Male sex and SLCO1B1 c.463C→A polymorphism together influenced rifampin AUC0–24 hour (R2 = 0.52) and weight‐normalized clearance (R2 = 0.65). All four volunteers with rifampin Cmax less than 8 μg/ml (lower end of the normal range) had c.463CA genotype. Rifampin Cmax and AUC0–24 hour had no significant relationship with the efavirenz AUC0–24 hour ratio or weight‐normalized clearance ratio in the presence versus absence of rifampin (p>0.05). Conclusions Men with the SLCO1B1c.463CA genotype are at increased risk of lower rifampin plasma exposure. However, plasma rifampin concentrations did not correlate with the extent of induction of efavirenz clearance by rifampin during coadministration.